(untitled) (Journal of Engineering, 2006)
The research explain The Effect of Domes Geometry Formation (size, shape,..) on Acoustic Performance, that for importance of this element in designing aspect specially in Islamic architecture and in the mosques building. The research follow sound reflection diagrams to obtain graphic forms that explain the affection of various Geometry Formation on Acoustic Performance , after analyze the graphic forms the final conclusions are introduced to obtain a primary vision about a capability of dome and who deal with it.